When facets meet impurities: Trace gas dominance over CO2 adsorption on ZnO - Bhati, Meema; Joshi, Kavita (Applied Surface Science, 2026)
The catalytic hydrogenation of CO2 to methanol using Cu-ZnO/Al2O3 (CZA) is a key route for sustainable chemical production, when coupled with CO2-rich industrial off-gases. However, trace secondary gases, though present only at ppm levels, can poison active sites and suppress catalytic performance. In this work, we employ periodic density functional theory (DFT) to investigate interactions of H2S, SO2, NO2, NO, CO and CH4 with ZnO surfaces:(10(-)10), (10(-)11), (11(-)20), (10(-)13), and (11(-)22), and compared their adsorption pattern with CO2, the principle component of methanol synthesis. H2S dissociates on all the surfaces, SO2, and NO2 are chemisorbed, CH4 remains physisorbed, and NO, CO, and CO2 exhibit facet-dependent adsorption. Electronic structure analysis reveal that chemisorption occurs when surface energy states near the Fermi level overlap with HOMO of adsorbate, enabling charge transfer, whereas physisorption lacks such overlap. The adsorption strength follows the order: H2S SO2 NO2 NO CO CO2 CH4, suggesting that sulfur and nitrogen containing species exhibit strong chemisorption and compete with CO2 for active sites, potentially impacting the efficiency of methanol synthesis. These insights provide an atomic scale understanding of impurity-surface interactions and highlight potential role of ZnO as an efficient feed stock purifier for CO2-rich gas streams.
Keywords: CZA catalyst; flue gases; Valorization of CO2; ZnO